PENGEMBANAGAN MEDIA AJAR KOMIK DIGITAL BERBASIS KEARIFAN LOKAL JEMBRANA PADA KONSEP PENDIDIKAN PANCASILA SISWA KELAS III SD - Ni Putu Cintya Ratna Dewi; I Made Aditya Dharma; Febryan Irwan (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Media development for Pancasila Education in third grade at SDN 2 Tegal Badeng Barat is still limited to media that lack innovation and context, resulting in low student interest in learning. This research aimed to produce digital comics based on Jembrana’s local wisdom for Pancasila Education material for third-grade students. The novelty of this research lies in the integration of Jembrana’s local wisdom values into digital comic media to provide more contextual learning. The study utilized the Research and Development (R&D) method based on the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The study subjects included 33 students and 1 teacher. Data were gathered by conducting observations, interviews, documentation, and questionnaires. The findings demonstrated that the designed media achieved a “highly valid” validity level, with a media expert validation score of 90% and a content expert validation score of 90%. During the implementation phase, the media received positive feedback because it fostered learning interest, facilitated understanding of the material, and encouraged student participation during learning. Thus, the digital comic based on Jembrana’s local wisdom was deemed “highly suitable” for use as an alternate teaching medium for Pancasila Education in elementary schools. ABSTRAK Perkembangan media pembelajaran Pendidikan Pancasila di kelas III SDN 2 Tegal Badeng Barat masih terbatas pada media yang kurang inovatif serta kontekstual, yang berakibat pada minimnya minat belajar siswa. Penelitian ini dimaksudkan guna mengembangkan komik digital berbasis kearifan lokal Jembrana pada materi Pendidikan Pancasila siswa kelas III. Kebaruan penelitian terletak pada pengintegrasian nilai-nilai kearifan lokal Jembrana pada media komik digital untuk menghadirkan pembelajaran yang lebih kontekstual. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE, mencakup tahapan analysis, design, development, implementation, serta evaluation. Subjek yang ditetapkan mencakup 33 siswa dan 1 guru. Data dihimpun dengan menjalankan observasi, wawancara, dokumentasi, dan angket. Temuan penelitian memperlihatkan, media yang dirancang menghasilkan tingkatan validitas “sangat valid” dengan skor validasi ahli media senilai 90% serta ahli materi senilai 90%. Pada tahap implementasi, media memperoleh respons positif sebab dapat mengembangkan minat belajar, memudahkan pemahaman materi, serta mendorong partisipasi siswa saat belajar. Dengan demikian, komik digital berbasis kearifan lokal Jembrana dinilai “sangat layak” dimanfaatkan sebagai alternatif media ajar Pendidikan Pancasila di sekolah dasar.